Language as a symbol of national identity in the context of the Russian-Ukrainian conflict - Homon, Andrii; Biletska, Iryna (LLC "Scientific Journals", 2024)
The relevance of this study lies in the fact that in the context of the Russian-Ukrainian war, language has become a key factor in national identity. The transition of a large part of the population to the Ukrainian language highlights changes in public attitudes and helps to strengthen national identity. The purpose of this study was to analyse language as a determinant of national identity in Ukraine in wartime. For this, 28 studies were reviewed, which were pre-selected according to the search criteria. The study found that language is primarily an instrument of territorial boundaries separating the aggressor country from Ukraine. During the Russian-Ukrainian war, a considerable number of Ukraine’s population became Ukrainian-speaking, which also affected the national identity of society. These changes are particularly relevant to those areas that were the primary target of the Russian invasion. This once again underlined the change in the population’s views under the influence of hostilities. Therewith, the aggressor country has long been trying to impose the Russian language on the Ukrainian population to change national identity. However, as the results of the analysis showed, Ukrainian national identity and Russian national identity differ in all aspects, which had the opposite effect during the full-scale invasion on 24 February 2022, or rather, the change in the population’s course towards Ukrainian national identity. However, the language conflict has not been fully resolved, and it affects the identity and self-awareness of Ukrainians, as there is still a part of the population that speaks Russian and Ukrainian–Russian pidgin. The study also found that not only the Ukrainian spoken language plays an essential role, but also the written language, especially during the Russian-Ukrainian conflict. Therefore, the findings of this study are of practical significance, as they can be used in practice by the Ukrainian government in developing measures for further language policy and resolving the internal language conflict of the population.

Актуальність дослідження полягає в тому, що в умовах російсько-української війни мова стала ключовим фактором національної ідентичності. Перехід значної частини населення на українську мову підкреслює зміни в суспільних поглядах та сприяє зміцненню національної самосвідомості. Метою дослідження був аналіз мови, як детермінанту визначення національної ідентичності в Україні в воєнних умовах. Для цього було проаналізовано 28 досліджень, які були попередньо відібрані за критеріями пошуку. В результаті дослідження встановлено, що мова перш за все є інструментом територіальних меж, що відділяє країну-агресора від України. В ході російсько-української війни значна кількість населення України стала україномовною, що також вплинуло на національну ідентичність суспільства. Особливо такі зміни стосуються тих областей, які були головною ціллю російського вторгнення. Це ще раз підкреслило зміну поглядів населення під впливом воєнних дій. При цьому країна-агресор довготривалий час намагалась нав’язати російську мову українському населенню із метою зміни національно ідентичності. Проте, як показали результати аналізу, українська національна ідентичність та російська національна ідентичність відрізняються у всіх аспектах, що й дало зворотний ефект при повномасштабному вторгненні 24 лютого 2022 року, а точніше зміна курсу населення до української національної самосвідомості. Проте мовний конфлікт повністю не вирішено, це впливає на ідентичність та самосвідомість українців, оскільки все ще є частина населення яка розмовляє російською мовою та суржиком. Також в результаті дослідження визначено, що важливу роль відіграє не лише українська усна мова, але й письмова, особливо під час російсько-українського конфлікту. Отже, результати даного дослідження мають практичне значення, оскільки та можуть використовуватися в практичній діяльності керівництвом України в процесі розроблення заходів подальшої мовної політики країни та вирішення мовного внутрішнього конфлікту населення.
Мова як символ національної ідентичності в умовах російсько-українського конфлікту
Keywords: self-consciousness; struggle for independence; military and political conditions; cultural policy; everyday communication; самосвідомість; боротьба за незалежність; військово-політичні умови; культурна політика; повсякденне спілкування